Stability of low-dimensional materials as novel supports in electrocatalysis - Nurul Hany Binte Mohammed Roslie (Nanyang Technological University, 2023)
In recent years, there has been a significant rise in research done to discover various novel support materials in electrocatalysis, with one of the most relevant applications being fuel cells. Promising support materials are low-dimensional carbon-based materials such as; two-dimensional (2D) graphene, and one-dimensional (1D) carbon nanotubes (CNTs). These materials are deemed promising due to their excellent properties in conductivity and electrochemical stability. Despite this, there is still a lack of understanding of how stable such materials are in realistic reaction conditions and there is little clarity on the dynamic processes that occur which bring about their exceptional electrochemical properties. In this project, 2D graphene, N-doped graphene and 1D carbon nanotubes were investigated to observe in real-time, the dynamic processes and response with the use of in situ liquid cell transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The findings from this project aim to qualitatively provide a baseline understanding of the stability of low-dimensional materials through in situ electrochemical reactions and visual analysis, ultimately showing that it can be a viable alternative for support materials in electrocatalysis.